From Subject to Citizen : the Second Empire and the Emergence of Modern French Democracy. - Hazareesingh, Sudhir (Princeton : Princeton University Press, 2014)
From Subject to Citizen offers an original account of the Second Empire (1852-1870) as a turning point in modern French political culture: a period in which thinkers of all political persuasions combined forces to create the participatory democracy alive in France today. Here Sudhir Hazareesingh probes beyond well-known features of the Second Empire, its centralized government and authoritarianism, and reveals the political, social, and cultural advances that enabled publicists to engage an increasingly educated public on issues of political order and good citizenship. He portrays th.
""Cover ""; ""Contents""
Print version record.
Cover; Contents.
JSTOR
Keywords: Political culture -- France -- History -- 19th century; Democracy -- France -- History -- 19th century; France -- History -- Second Empire, 1852-1870.; France -- Histoire -- 1852-1870 (Second Empire); HISTORY -- Europe -- France; Democracy; Political culture; France; 1800-1899; History